Description of the Characteristics of Barriers to Pain Comfort: Sleep Quality in Elderly with Rheumatoid Arthritis in Kendal Regency - Rina Anggraeni; Villayatina Villayatina; Riani Pradara Jati; Qurrotul Aeni; Andriyani Mustika Nurwijayanti (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Someone who has reached the age of 60 years and over often appears various disorders, one of the disorders experienced by the elderly is joint pain or bone disease known as Rheumatoid arthritis. Joint pain caused by inflammation of the joints that are swollen or damaged has occurred, causing pain and making people with Rheumatoid Arthritis afraid to move so that it interferes with their activities. Barriers to pain comfort in the elderly with Rheumatoid Arthritis are characterized by sleep quality characteristics. This study aims the Characteristics Pain comfortf Barriers of sleep quality in the Elderly with Rheumatoid Arthritis in Gebanganom Village, Kendal Regency. The research design is a quantitative descriptive research. The study population was 49 elderly people. The research sample was 49 elderly people with total sampling technique. Data collection used a pain scale questionnaire, a PSQI (Pitssburgh Sleep Quality Index) questionnaire. The results of this study showed that the pain level was mild (8.16%), the majority of respondents had moderate pain level (73.47%), and severe pain level (18.37%), the majority of respondents had good sleep quality (71.43%), and poor sleep quality (28.57%),